The facilitation of motor actions by acoustic and electric stimulation - Marinovic, Welber; Milford, M.; Carroll, T.; Riek, S. (Wiley-Blackwell Publishing, Inc., 2015)
The presentation of a loud acoustic stimulus during the preparation of motor actions can both speed movement initiation and increase response vigor. Several recent studies have explored this phenomenon as a means to investigate the mechanisms and neural correlates of movement preparation. Here, we sought to determine the generality of this effect across sensory modalities, and in particular whether unexpected somatosensory stimulation can facilitate movements in a manner similar to loud sounds. We show that electric and acoustic stimuli can be similarly effective in inducing the early release of motor actions, in both reaction time and anticipatory timing tasks. Consistent with recent response activation models of motor preparation, we also demonstrate that increasing the intensity of electric stimuli induces both progressive decreases in reaction time and increases in response vigor. Additionally, we show that the early release of motor actions can be induced by electric stimuli targeting predominantly either muscle afferents or skin afferents. Finally, we show that simultaneous acoustic and electric stimulation leads to earlier releases of anticipatory actions than either unimodal stimulus. These findings may lead to new avenues for experimental and clinical exploitation of the effects of accessory sensory information on movement preparation and initiation.